UNDERSTANDING THE NEOCLASSICAL THEORY OF ADMINISTRATION (CIPEEX, 2025)
The Neoclassical Theory of Administration emerged in the 1950s as a response to the economic and social transformations of the post-World War II period, seeking to synthesize the emphasis on structure and efficiency of the Classical Theory with the valorization of the human factor from the Human Relations Theory. This approach recognizes organizations as complex systems composed of formal and informal elements that interact to achieve predefined objectives. The methodology adopted consists of extensive bibliographic research, including works by authors such as Peter F. Drucker and Idalberto Chiavenato. The fundamental principles of the Neoclassical Theory are explored, including the importance of division of labor, hierarchy, and specialization, which aim to maximize organizational efficiency. Although the approach faces criticism, especially regarding autocracy and the imposition of goals, the careful implementation of Management by Objectives (MBO) can prove to be an effective tool for increasing employee motivation and engagement. This article concludes that the Neoclassical Theory remains relevant for organizational management, providing a solid foundation to address the challenges of the dynamic environment of contemporary organizations.
Keywords: Neoclassical Theory of Administration; Management by Objectives; Organizational efficiency; Human factor; Motivation.